2019
DOI: 10.1016/j.neuroimage.2018.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Neural dynamics of verbal working memory processing in children and adolescents

Abstract: Development of cognitive functions and the underlying neurophysiology is evident throughout childhood and adolescence, with higher order processes such as working memory (WM) being some of the last cognitive faculties to fully mature. Previous functional neuroimaging studies of the neurodevelopment of WM have largely focused on overall regional activity levels rather than the temporal dynamics of neural component recruitment. In this study, we used magnetoencephalography (MEG) to examine the neural dynamics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 49 publications
(87 reference statements)
4
38
0
1
Order By: Relevance
“…The working memory process is often described in three phases: 1) encoding: processing and storing the incoming stimuli; 2) maintenance: rehearsing the items in the memory store; and 3) retrieval: recovering the items in the memory store for use or manipulation. Recent studies have sought to clarify the dynamic neural patterns that underlie each phase of verbal working memory processing ( Embury et al, 2019 , Heinrichs-Graham and Wilson, 2015 , Proskovec et al, 2016 , Proskovec et al, 2019 , Roux and Uhlhaas, 2014 ). During encoding, there is a strong desynchronization in the alpha–beta frequency (10–18 Hz) that begins in the bilateral occipital cortices, and then extends into the left lateral parietal, temporal, and inferior frontal cortices in turn.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The working memory process is often described in three phases: 1) encoding: processing and storing the incoming stimuli; 2) maintenance: rehearsing the items in the memory store; and 3) retrieval: recovering the items in the memory store for use or manipulation. Recent studies have sought to clarify the dynamic neural patterns that underlie each phase of verbal working memory processing ( Embury et al, 2019 , Heinrichs-Graham and Wilson, 2015 , Proskovec et al, 2016 , Proskovec et al, 2019 , Roux and Uhlhaas, 2014 ). During encoding, there is a strong desynchronization in the alpha–beta frequency (10–18 Hz) that begins in the bilateral occipital cortices, and then extends into the left lateral parietal, temporal, and inferior frontal cortices in turn.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this neural response pattern has been shown to increase in amplitude and become more widespread as a function of working memory load, suggesting that these oscillatory dynamics are crucial for proper stimulus encoding ( Proskovec et al, 2019 ). In addition, there is a narrow, robust synchronization in the lower alpha (8–12 Hz) frequency that emerges in the bilateral superior parieto-occipital cortices during maintenance and dissipates at the onset of retrieval, which has been shown to be associated with the active inhibition of distractors ( Bastiaansen et al, 2002 , Bonnefond and Jensen, 2013 , Embury et al, 2019 , Proskovec et al, 2019 , Roux and Uhlhaas, 2014 ). In sum, there is the wealth of spatiotemporal oscillatory behavior that is elicited during the performance of a verbal working memory task.…”
Section: Introductionmentioning
confidence: 99%
“…The sexually dimorphic alpha responses identified in the present study again demonstrate female-specific recruitment of parietal association areas often involved in attention and higher-order processing, though unlike the gamma band results, these sex differences did not vary with age. Alpha activity has been documented to vary by age and sex during verbal working memory processing ( Embury et al, 2019 ); however, most MEG studies of cognitive development have observed these interactions in other frequency bands ( Fung et al, 2020 ; Killanin et al, 2020 ; Taylor et al, 2020 ). Future studies could utilize different visual stimuli or include further attentional manipulations to determine the extent to which alpha activity during basic visual perception exhibits developmental alterations, or whether such maturational effects are limited to more complex tasks and other oscillatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Maturation of neural activity serving higher-order cognitive processing during adolescence has been extensively studied using fMRI (for review, see Casey et al, 2005 ; Rubia, 2013 ), and studies have identified sex-specific developmental patterns of cortical network activity during complex visuospatial processing tasks in youth, such as mental rotation and spatial working memory ( Hugdahl et al, 2006 ; Kucian et al, 2007 ; Schweinsburg et al, 2005 ). There is also a growing wealth of knowledge regarding changes in childhood neural oscillatory dynamics serving motor control ( Gaetz et al, 2010 ; Heinrichs-Graham et al, 2018 , 2020 ; Trevarrow et al, 2019 ; Wilson et al, 2010 ), higher-order cognition ( Embury et al, 2019 ; Taylor et al, 2020 ; 2021 ), and more complex visuospatial attention ( Fung et al, 2020 ; Killanin et al, 2020 ). Executing these tasks obviously requires input and integration of basic sensory information for successful performance.…”
Section: Introductionmentioning
confidence: 99%
“…This was done by first computing voxel-wise correlations between age and spectrally specific neural activity within each group and then comparing the resulting statistical maps group-wise using a whole-brain Fisher Z transformation. 4,12,21 Individual participant-level maps that contained significant artifacts were excluded frequency-wise at this step; however, all statistical balancing of group, age, and group-by-age effects on demographic factors remained intact following these exclusions. From the resulting significant clusters of neural activity, pseudo-t values per participant were extracted from the peak voxel (i.e., the voxel with the highest statistical value per cluster), and these were used in post hoc testing of interaction effects and targeted hypotheses.…”
Section: Meg Image Reconstruction and Statistical Analysismentioning
confidence: 99%